The Relationship of Bristle Worm, Protodorvillea kefersteini (McIntosh, 1869) (Eunicida, Dorvilleidae) Abundance with Environmental Variables in Çardak Lagoon (Turkish Straits) Exposed to domestic Discharge - Yeşim Büyükateş; Seçil Acar; A. Suat Ateş; Ertan Dağlı (Aquatic Sciences and Engineering)
This study presents the correlations between opportunistic polychatea, Protodorvillea kefersteini (McIntosh, 1869) abundance, and environmental variables in Çardak Lagoon. Samplings were carried out on the bottoms using a 30x30 cm quadrate seasonally between 1 and 1.8 m depths of seven sampling points in October 2018, February, April, and June 2019. A total of 1094 specimens belonging to P. kefersteini were collected. Environmental variables such as gravel content in sediment, pH, and salinity levels in the water had the highest correlations with the abundance through the sampling periods. Considering the sampling points, the highest correlation value was between water salinity and the abundance. Sediment gravel content, pH, salinity, temperature, anionic surfactant levels, and NO2+NO3 were major environmental variables affecting P. kefersteini abundance in the study area spatially and temporally.